Prognostic value of polarized macrophages in patients with hepatocellular carcinoma after curative resection. Issue 6 (4th February 2016) - Shu, Qing‐Hua; Ge, Yong‐Sheng; Ma, Hua‐Xing; Gao, Xiao‐Qiang; Pan, Jing‐Jing; Liu, Dong; Xu, Ge‐Liang; Ma, Jin‐Liang; Jia, Wei‐Dong
Abstract: As the most predominant tumour‐infiltrating immune cells, tumour‐associated macrophages (TAMs) are significant for fostering tumour growth, progression and metastasis. CD68‐positive TAMs display dissimilarly polarized programmes comprising CD11c‐positive pro‐inflammatory macrophages (M1) and CD206‐positive immunosuppressive macrophages (M2). The aim of this study is to determine the prognostic significance of diametrically polarized TAMs in hepatocellular carcinoma (HCC) and their application to risk stratification of patients according to their specific prognostic values. This study included 80 consecutive patients with HCC, and we evaluated diametrically polarized functional status of macrophages by immunohistochemical staining of CD68, CD11c and CD206. Prognostic values and clinicopathologic features were assessed in these patients. High versus low CD11c‐positive TAM density ( P = 0.005) and low versus high CD206‐positive TAM density ( P = 0.002) were associated with better overall survival, whereas CD68‐positive TAM density had no prognostic significance (low versus high, P = 0.065). Furthermore, the presence of these positive staining macrophages did not show any prognostic significance for recurrence‐free survival (all P > 0.05). Multivariate Cox regression analysis identified CD11c‐positive and CD206‐positive TAMs as an independent prognostic factor ( P < 0.001, P = 0.031, respectively). Intratumoural infiltration of diametrically polarized TAMs, a novel identified independent prognostic factor for survival in patients with HCC, could be combined with the TNM stage and the Barcelona Clinic Liver Cancer stage to improve a risk stratification system.